A comparative study review: The performance of Savonius-type rotors - Al-Gburi K.A.H.; Alnaimi F.B.I.; Al-quraishi B.A.; Sann Tan E.; Maseer M.M. (Elsevier Ltd, 2023)
Environmental technology; Blade profile; Comparatives studies; Environmental pollutions; Optimisations; Renewable energies; Rotor performance; Savonius rotor; Savonius turbine; Variable-parameters; Energy harvesting